Improved Growth Media for Isolation and Identification of Fish Pathogenic Tenacibaculum spp. - Erwan Lagadec; Ingeborg Emilie Berg Kahrs; Kathleen Frisch; Henrik Duesund; Are Nylund; Sverre Bang Småge (Microorganisms)
Standard blood agar medium with 2% NaCl (BAS) and Marine Agar (MA) are commonly used in bacteriological investigations of winter ulcers in farmed Atlantic salmon (Salmo salar Linnaeus) in Norway and allow easy recovery of Moritella viscosa based on its characteristic viscous colonies and β-hemolytic activity. However, the recent increase in cases of winter ulcers involving Tenacibaculum spp. and the potential emergence of T. maritimum due to rising temperatures highlight the need for improved methods of isolation and identification. Indeed, the recovery of Tenacibaculum spp. from outbreaks of winter ulcers or tenacibaculosis can be challenging. Despite the development of several agar media over the years to overcome this issue, such as Flexibacter maritimus medium (FMM), it remains difficult to differentiate Tenacibaculum species. We evaluated the growth dynamics and phenotypic characteristics of 13 bacterial isolates commonly associated with ulcer outbreaks on five different agar media, including two new formulations: kanamycin-supplemented marine blood agar for the selective isolation of Tenacibaculum spp. (KABAMA) and general blood agar for marine bacteria (BAMA). These new media facilitate the identification of Tenacibaculum spp., including T. maritimum, by distinguishing colonies based on their specific color, shape, and hemolytic activity.